Dispersion, Accumulation, and the Ultimate Fate of Microplastics in Deep-Marine Environments: A Review and Future Directions - Kane, Ian A.; Clare, Michael A. (Frontiers in Earth Science, 2019)
An estimated 8.3 billion tonnes of non-biodegradable plastic has been produced over the last 65 years. Much of this is not recycled or disposed of ‘properly’, has a long environmental residence time and accumulates in sedimentary systems worldwide, posing a threat to important ecosystems and potentially human health. We synthesise existing knowledge of seafloor microplastic distribution, and integrate this with process-based sedimentological models of particle transport, to provide new insights, and critically, to identify future research challenges. Compilation of published data shows that microplastics pervade the global seafloor, from abyssal plains to submarine canyons and deep-sea trenches. However, few studies relate microplastic accumulation to sediment transport and deposition. Microplastics may enter directly into the sea as marine litter from shipping and fishing, or indirectly via fluvial and aeolian systems from terrestrial environments. The nature of the entry-point is critical to how terrestrially-sourced microplastics are transferred to offshore sedimentary systems. We present models for physiographic shelf connection types related to the tectono-sedimentary regime of the margin. Beyond the shelf, the principal agents for microplastic transport are: i) gravity-driven transport in sediment-laden flows; ii) settling, or conveyance through biological processes, of material that was formerly floating on the surface or suspended in the water column; iii) transport by thermohaline currents, either during settling or by reworking of deposited microplastics. We compare microplastic settling velocities to natural sediments to understand how appropriate existing sediment transport models are for explaining microplastic dispersal. Based on this analysis, and the relatively well-known behaviour or deep-marine flow types, we explore the expected distribution of microplastic particles, both in individual sedimentary event deposits and within deep-marine depositional systems. Residence time within certain deposit types and depositional environments is anticipated to be variable, which has implications for the likelihood of ingestion and incorporation into the food chain, further transport, or deeper burial. We conclude that integration of process-based sedimentological and stratigraphic knowledge with insights from modern sedimentary systems, and biological activity within them, will provide essential constraints on the transfer of microplastics to deep-marine environments, their distribution and ultimate fate, and the implications that these have for benthic ecosystems.